A Concise Review of Recent Advancements in Carbon Nanotubes for Aerospace Applications - Silvia Zecchi; Giovanni Cristoforo; Erik Piatti; Daniele Torsello; Gianluca Ghigo; Alberto Tagliaferro; Carlo Rosso; Mattia Bartoli (Micromachines)
Carbon nanotubes (CNTs) have attracted significant attention in the scientific community and in the industrial environment due to their unique structure and remarkable properties, including mechanical strength, thermal stability, electrical conductivity, and chemical inertness. Despite their potential, large-scale applications have been limited by challenges such as high production costs and catalyst contamination. In aerospace applications, CNTs have demonstrated considerable promise either in the form of thin layers or as reinforcements in polymer and metal matrices, where they enhance mechanical, thermal, and electromagnetic performance in lightweight composites. In this short review, we provide an overview of CNTs’ properties and structures, explore CNT growth methods, with a focus on chemical vapor deposition (CVD), and examine their integration into aerospace materials both as films and as multifunctional reinforcements.